(untitled) (CIPEEX, 2025)
The renal system is essential for regulating the body’s homeostasis, regulating blood pressure, electrolyte balance, and the elimination of toxic substances. When these functions are compromised, the body needs to use medications with specific mechanisms to restore balance. Hydrochlorothiazide is a drug widely used in this context, due to its diuretic action. This abstract aims to present the action of hydrochlorothiazide in blood pressure control and edema treatment, highlighting its diuretic function. A literature review was conducted using the PUBMED and Cochrane Database of Systematic Reviews databases. The articles included were those available free of charge in Portuguese or English. Those excluded were those that dealt with the combined use of hydrochlorothiazide and another drug or its application in cases of renal pathologies. Hydrochlorothiazide is a thiazide-type diuretic drug that promotes greater elimination of sodium and water from the body. Thiazides act directly on the sodium chloride cotransporter in the distal convoluted tubules of the renal nephrons, inhibiting their reabsorption action, thereby promoting natriuretic and diuretic effects. Hydrochlorothiazide is effective in antihypertensive therapy and in reducing peripheral edema by reducing plasma and extracellular volumes, in addition to reducing cardiac output and peripheral resistance. The advantages of using hydrochlorothiazide in reducing blood pressure and peripheral edema have been shown to be effective in clinical trials, especially in initial treatment, however, it does not replace individualized treatment plans.